2021
DOI: 10.3390/app11188392
|View full text |Cite
|
Sign up to set email alerts
|

First Report and 3D Reconstruction of a Presumptive Microscopic Liver Lipoma in a Black Barbel (Barbus balcanicus) from the River Bregalnica in the Republic of North Macedonia

Abstract: A lipoma is a benign tumour of mature adipocytes which may appear in various species, including marine and freshwater fish. It usually occurs in isolated locations, such as a superficial or deep mass, mainly in the skin and seldom in other organs. In non-mammalian vertebrates, there is no agreed minimal size for the mass to be considered a lipoma. This study histologically describes a case proposed to be a microlipoma in the liver of Barbus balcanicus. The structure was an oval-shaped mass of well-differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Three published manuscripts used histopathological methodology to investigate tissues of interest on various cyprinid fish from ecosystems of the Balkan Peninsula. The case study of lipoma found in the liver of the black barbel (Barbus balcanicus) in the Bregalnica River (North Macedonia) was described by Rebok et al [14]. This agglomerate of adipocytes was assessed microscopically after being serially sectioned, while the authors also reconstructed a 3D image after applying software.…”
Section: Environmental Studiesmentioning
confidence: 99%
“…Three published manuscripts used histopathological methodology to investigate tissues of interest on various cyprinid fish from ecosystems of the Balkan Peninsula. The case study of lipoma found in the liver of the black barbel (Barbus balcanicus) in the Bregalnica River (North Macedonia) was described by Rebok et al [14]. This agglomerate of adipocytes was assessed microscopically after being serially sectioned, while the authors also reconstructed a 3D image after applying software.…”
Section: Environmental Studiesmentioning
confidence: 99%
“…In most cases, lipomas are solitary and are located subcutaneously, or intramuscularly. However, localized lipomas have also been reported in organs such as kidney and liver (Rebok et al, 2021). Lipomas have even been observed in the spleen of perch (Stejskal et al, 2016).…”
mentioning
confidence: 99%